Пёстрая сорока: стихи : перевод с удмуртского / Андрей Самсонов - Самсонов Андрей Александрович (Удмуртия, 2008)
Экземпляры: М/а ДБ (20180117) / Инвентарный номер: 107319 / Цена: 8.00 / Авт.знак: С 17 / ГРНТИ: 17.82 / ББК: Д